Getting the message across : communication with diverse populations in clinical genetics - Wiggins, Jennifer; Middleton, Anna (Oxford University Press, 2013)
Communicating with patients about genetic concepts is fraught with complications. In addition to the hazy takeaway messages and the likelihood of peripheral findings, the diverse cultural backgrounds of patients in a genetics clinic present another layer of challenge for clinicians and genetic counselors in their aim to communicate important findings effectively and respectfully. This book provides practical advice to assist genetic counselors, geneticists, and other health professionals wanting to engage appropriately with different clients from different communities -- patients who are heari.